Specifics of Investment in Emerging Real Estate Markets - Case studies of private dormitories in Warsaw and Prague - Walawender, Weronika (2019)
The main goal of this Master Thesis is to investigate Commercial Real Estate investments in Emerging Real Estate markets in Central Eastern Europe, using case study as a research method. The specifics of Real Estate investments in this region are described based on examples of private dormitory projects in two Central Eastern European cities: Warsaw and Prague. The thesis looks on both general and country-specific aspects of investing in commercial Real Estate, taking into account both macroeconomic indicators and financial methods, such as Discounted Cash Flow Model and Investment Criteria. After evaluating both financial indicators and market situation in Warsaw and Prague, recommendations regarding profitability of private dormitory projects in those two cities are provided. Furthermore, advantages, drawbacks and limitations of different ways of comparing Commercial Real Estate investments are included in the analysis.